Dissemination of systematic reviews in a hospital setting: a comparative survey for spreading use of the Cochrane Library. Issue 1043 (12th May 2012) - Weng, Yi-Hao; Hsu, Chih-Cheng; Shih, Ya-Hui; Lo, Heng-Lien; Chiu, Ya-Wen; Kuo, Ken N
Abstract : Introduction: The Cochrane Library is the most important online evidence retrieval database of systematic reviews. Since 2007, the National Health Research Institutes has offered Taiwan's regional hospitals free access to the Cochrane Library. This study investigated how these hospitals disseminate its utilisation. Methods: The usage rate of Cochrane reviews was measured in the participating hospitals from January 2008 to December 2009. Thereafter, a questionnaire survey was conducted for each regional hospital disseminator at the beginning of 2010 to analyse their methods of disseminating Cochrane reviews. Results: The hospitals were stratified into three groups according to the relative rate of access: high (n=15), medium (n=16) and low (n=13). In comparison with the low-usage hospitals, the high-usage hospitals tended to assign a disseminator of evidence-based medicine to take charge of the dissemination of Cochrane reviews (p<0.001). In addition, the high-usage hospitals more often used the following six methods: providing relevant information via email (p<0.05), investing in early adopters (p<0.05), using assistance from designated personnel (p<0.05), highlighting the activity of early adopters (p<0.05), conducting workshops (p=0.001), and inviting experts to speak (p<0.001). There was no significant difference between high- and low-usage hospitals in organisational barriers. Conclusion: This study has identified several helpful strategies used by Taiwan's hospitals to enhance dissemination of the Cochrane Library, including raising of awareness, active delivery of information, mentoring relationships, and educational training. The data suggest that disseminating evidence-based medicine simultaneously is a key element.